Neutrino mean free path in neutron matter with Brussels-Montreal Skyrme functionals. Issue 1 (January 2016) - Pastore, A; Martini, M; Davesne, D; Navarro, J; Chamel, N; Goriely, S
Abstract: We calculate the neutrino mean free path in cold neutron matter with some modern Brussels-Montreal functionals. The three typical functionals used in this article produce quite different results implying a possible impact on the cooling mechanism of neutron stars.